A predictive study of the effect of some variables on perceived environmental disturbance - Aljanabi, Salam; Alnuaemi, Muhand (Al-Adab Journal, 2023)
Perceived Environmental Disorder is an interpreted state of the world in which things are atypical and incoherent. Conversely, a perceived order is an explanatory state of the world in which things are in stereotyped and coherent situations. According to the broken windows theory, crime does not arise out of a vacuum, but rather from the presence of encouraging factors, and the most prominent of these factors is the presence of chaos and order in human societies. The research sample consisted of 398 male and female university students on whom the Perceived Environmental Disorder Scale was applied and its factor structure was extracted using exploratory and confirmatory factor analysis. The results of the research revealed that the research sample developed a firm belief in the existence of a perceived environmental disturbance, both physical and social, and that 19.2% of the sample members admit that there is a very severe perceived environmental disorder, 60.8%. However, the demographic variables did not have a high contribution to predicting the degree and severity of environmental disturbance. perceived.